Assessing Land-Use Driven Soil Degradation Potential and Biomass Production Dynamics in the Corogrojong Sub Sub-Watershed, Malang, Indonesia - Shofie Rindi Nurhutami; Muchammad Bima Gegana Sakti; Zenny Faridatus Sa’diyah (Acta Solum, 2025)
Soil degradation poses a critical threat to agriculture and ecosystem sustainability in tropical watersheds. This study focuses on the Corogrojong Sub-Sub-Watershed, located in Indonesia's Upper Brantas Basin, to assess soil degradation potential using GIS-based analysis combined with biophysical parameters such as land use, slope gradient, annual rainfall, and soil type. A weighted overlay method was applied to map soil degradation potential and recommend mitigation strategies for sustainable biomass production. The findings show that only 9.9% (59.06 ha) of the area is classified as having very low degradation potential, while the remaining 90.1% falls under low to moderate potential, with low-potential areas covering 39.7% (235.69 ha) and moderate-potential areas 50.4% (299.37 ha). Despite the challenging terrain—where steep slopes (>40%) cover 46% of the area and highly erodible Andisols dominate 77.7%—the presence of agroforestry and forest systems significantly reduces degradation potential. However, this balance remains fragile, as the watershed’s stability relies on the preservation of these systems. Any loss of green cover due to land conversion could lead to extensive soil degradation. To mitigate this, the study proposes a zonal approach: active conservation efforts, including terracing, vetiver grass planting, and riparian filter strips in moderate-potential zones, and incentive-based mechanisms, such as Payment for Ecosystem Services (PES), in lower-potential areas to prevent land-use change. This study provides based for sustainable land management policies that harmonize agricultural development with ecosystem protection in the Upper Brantas Basin.